Reorder Point Analysis On Fasajaya Wholesale Store Inventory Using POM QM Application - Fadila Nurfauzia; Shinta Rizqiya (Journal of Bussines Management Basic, 2023)
Wholesale businesses are categorized as medium businesses within MSMEs, wholesale businesses are one of the businesses that have survived, for example during the Covid-19 pandemic. Among the small number of types of businesses that survived the pandemic, the wholesale business was one of the businesses that survived. It is not without reason that more people's activities at home during the pandemic have caused demand for basic necessities to increase. Wholesalers are also very easy to find, almost every village or sub-district has a wholesaler. Based on this, this research aims to analyze inventory control at Fasajaya wholesale stores, so that it will increase the fulfillment of consumer demand. This research uses the POM QM analysis tool to analyze the data. The results of this research are: From this data it can be seen that the results of the EOQ calculation include the average inventory in the Fasajaya store warehouse for Indomie chicken onion noodle products is 79 boxes, then for the reorder point or point from the reorder point is 53 dus. With these results, the Fasajaya wholesale store has a reordering standard that when the stock in the warehouse reaches 53 boxes then another reorder can be made